PENGARUH BEBERAPA TIPE PENGENDALIAN GULMA PADA PERUBAHAN STRUKTUR VEGETASI TUMBUHAN BAWAH DI PERKEBUNAN JABON (Neolamarckia cadamba (Roxb.) Bosser.) - Avry Pribadi (LPPM Universitas Negeri Jakarta, 2023)
Jabon (Neolamarckia cadamba (Roxb.) Boser.) is commonly planted for many purposes, such as furniture, raw material for industries, and land rehabilitations. Eventhough this tree has no significant pests and diseases, weed control treatments are required. Many weed control treatments are known to affect vegetation structure of weed. Thus, the objective of this study was to examine the effect of weed control treatments to the vegetation structure of weed under Jabon plantation. This study was conducted in Kecamatan Tanah Putih Tanjung Melawan, Kabupaten Rokan Hilir, Riau Province in 2012. Non Factorial Randomized Group Design with five replications was applied to perform the study. There were four treatments (glyphosate, paraquat, mixture of glyphosate and paraquat, and legume cover crop/LCC) and control. The results revealed that glyphosate and paraquat had the highest value in surpressing the weed growth as much as 34,45% and 31,11% (P>0.05) after one month application. Yet, after three months, LCC was significantly surpressed the number of weed (49,44%) (P<0.05) compared to other treatments. Among all weed species, Blumea sp. was the dominant species after one month of glyphosate and paraquat application. Nevertheless, application of glyphosate-paraquat mixture and LCC resulted Ottochloa nodosa as the dominant species after one month application.